Resource dependency and communication networks in Early Neolithic western Europe - Michael Kempf; Solène Denis (Quaternary Environments and Humans)
During the European Neolithisation Process, a pivotal facet of Neolithic population dynamics lay in the capability of agro-pastoral communities to procure high-quality raw material for stone tools. Whether this material was sourced from local geological units or got transported via large-scale communication networks is, however, not yet fully understood. To trace the distribution patterns of Early Neolithic resource dispersal, we present a multicomponent network analysis and the first resource dependency model of Middle Eocene lithic records across western Europe. The model builds on topographic landscape permeability and Bartonian silicite dispersal and estimates the Chaine Operatoire (CO) sequences from i) directly sourced raw material based on accumulative cost functions; ii) chronologically differentiated network models; iii) a probability model of potential site distributions based on a point process model (PPM). We resume that early Neolithic site locations were particularly targeted at connecting to the supraregional resource exchange network that originated from the Paris Basin. Local resource exploitation predominated in the core region of Bartonian silicite distribution whereas distant sites were located on or close to high-probability communication and network corridors. Particularly striking is the differentiation highlighted by the CO segmentation towards the end of the Early Neolithic with distinct patterns of clustered production, intermediate, and dispersed consumer sites. This indicates that major production centres can be expected in close distance to the resource with high consumer density in secondary centres in a star-shaped pattern across the study area.